Fabrication and Antitumor Mechanism of a Nanoparticle Drug Delivery System: Graphene Oxide/Chitosan Oligosaccharide/γ‐Polyglutamic Acid Composites for Anticancer Drug Delivery. Issue 43 (26th November 2019) - Liu, Baoqing; Che, Chengchuan; Liu, Jinfeng; Si, Meiru; Gong, Zhijin; Li, Yuan; Zhang, Junming; Yang, Ge
Abstract: This study focused on the design of a novel pH responsive nanoparticle drug delivery system (NDDS) with high biocompatibility and water solubility. The designed system was used for doxorubicin (DOX) delivery at tumor sites in a controlled manner. These innovative nanoparticles are soluble in physiological solutions besides water. In this study, pretreated γ ‐polyglutamic acid ( γ ‐PGA) aqueous solutions were loaded into composites of graphene oxide (GO) covalently linked with chitosan oligosaccharide (CO) to fabricate GO‐CO‐ γ ‐PGA via amidation. The characterizations of the synthesized samples were carried out by using fourier transform infrared spectrometer (FTIR), X‐ray photoelectron spectrometer (XPS), ultraviolet– visible spectrophotometer (UV‐Vis), transmission electron microscopy (TEM), atomic force microscope (AFM) and zeta potential. Furthermore, drug loading and release behaviors from GO‐CO‐ γ ‐PGA were studied. The DOX loading in the constructed nanocarriers (GO‐CO‐ γ ‐PGA‐DOX) resulted in controlled and sustained release. The results of cell experiments revealed that the synthesized composites, which were easily transferred into cells, showed low toxicity and exhibited excellent antitumor effect due to its good connection with DOX. In addition, the composite nanoparticles caused the cell cycle arrest of Hela cells at the G2 /M phase. Western blot results indicated that GO‐CO‐ γ ‐PGA‐DOX downregulated the expression of Bcl‐2 protein but upregulated Bax protein expression, which triggered the release of cytochrome C (Cytc). This condition further activated caspase‐3, cleaved the substrate of poly ADP‐ribose polymerase (PARP), and caused cell apoptosis. These results demonstrated that GO‐CO‐ γ ‐PGA‐DOX induces apoptosis via the intrinsic mitochondrial apoptotic pathway. Hence GO‐CO‐ γ ‐PGA composites have promising application in the field of biomedicine. Abstract : In order to prepare a novel drug delivery system, we modified GO with biological materials of CO and γ‐PGA, and the synthesized nanocarriers exhibited properties of high water solubility, drug loading capacity and efficiency, as well as pH triggered drug release. The composites can deliver DOX to cell nucleus, cause cell cycle arrest at G2 /M phase, and induce cell apoptosis via intrinsic mitochondrial apoptotic pathway.